High‐Resolution Computed Tomography Findings for Patients With Drug‐Induced Pulmonary Toxicity, With Special Reference to Hypersensitivity Pneumonitis‐Like Patterns in Gemcitabine‐Induced Cases. (12th February 2013) - Tamura, Masaki; Saraya, Takeshi; Fujiwara, Masachika; Hiraoka, Sayuki; Yokoyama, Takuma; Yano, Kinuko; Ishii, Haruyuki; Furuse, Junji; Goya, Tomoyuki; Takizawa, Hajime; Goto, Hajime
Abstract : Background: Gemcitabine (GEM) is widely used as a chemotherapeutic agent. However, pulmonary toxicity has been rarely observed with GEM use. This article aims to determine the incidence and causes of drug‐induced pulmonary toxicity, and to classify the high‐resolution computed tomography (HRCT) findings for antitumor therapy‐associated pulmonary toxicity based on characteristic patterns and pathological considerations, with a special focus on GEM‐associated pulmonary toxicity (GAPT). Methods: Medical records of all patients with drug‐induced pulmonary toxicity seen at Kyorin University hospital between April 2006 and December 2011 were retrospectively reviewed. The study examined correlations between HRCT and the assessed pathological or clinical findings, with a specific focus on antitumor drugs. Results: We identified 66 patients with drug‐induced pulmonary toxicity. Among the antitumor drugs, GEM was the primary offending agent ( n = 8) for pulmonary toxicity followed by docetaxel and gefitinib. HRCT patterns for the eight GAPT patients included the non‐specific interstitial pneumonia (NSIP; n = 5) and the hypersensitivity pneumonitis (HP)‐like pattern ( n = 3). In contrast, four patients in the study were found to have the HP‐like pattern, with three cases associated with GEM and one case associated with imatinib mesylate. The transbronchial lung biopsy or video‐assisted thoracic surgery specimens for these patients showed granuloma or organizing tissue with a random distribution that was independent of the respiratory bronchiole. These results appeared to correspond to the HRCT‐determined centrilobular nodules. Conclusion: GEM was the leading cause of drug‐induced pulmonary toxicity in the patients examined in this study. This toxicity appears as NSIP or an HP‐like pattern during HRCT examinations. This HP‐like pattern may be useful for diagnosing GEM‐induced pulmonary toxicity, as well as demonstrating granuloma or organizing tissue during lung pathology examinations. Abstract : This retrospective study examines the incidence and causes of drug‐induced pulmonary toxicity and classifies high‐resolution computed tomography findings for antitumor‐therapy associated pulmonary toxicity based on characteristic patterns and pathological considerations, with a special focus on gemcitabine‐induced pulmonary toxicity.